Communication and meaning construction in teacher education: work by many hands - Tania Maria Esperon Porto; Maristani Polidori Zamperetti; Lourdes Helena Rodrigues dos Santos (Universidade Federal de Santa Maria, 2014)
This text aims to bring a crop of three processes of research conducted in different contexts: two public schools in elementary and high school and a public university, with the confluence of the experience of communication, sharing and collaborative construction of meaning experienced by us, educators and researchers. We talked to teachers and the media and their languages. We have lived and investigated processes of teacher training in communicative methodology, which made it possible to create experiences, to ask questions and reflections about everyday teaching, treated in the light of theoretical education and communication. The communication practices provided practical experiences of the world, reveal directions of teachers, allowing an interaction between subject and their contexts. Working among several different people is to provide means to cope with complex situations that individually we can not manage.